ANALISIS FAKTOR DALAM DAN LUAR NEGERI TERHADAP JAKARTA ISLAMIC INDEX (JII) PERIODE 2010-2021 - Furqonul Haq (Faculty of Economics and Business, 2023)
This study aims to examine domestic and foreign factors on the Jakarta Islamic Index (JII) using the estimated Vector Error Correction Model. Monthly data used from January 2010 to December 2021 (144 months). This research generally gets two findings. First, in the long term domestic factors (exchange rates) and foreign factors (world oil prices, world gold prices and DJIMI) have a significant positive influence on JII. Second, in the long run domestic factors (inflation) and foreign factors (KLSE) have a significant negative influence on JII. This research is expected to provide benefits for academics and researchers who are interested in examining the factors that influence the Islamic capital market index in Indonesia.